Release the BEESTS: Bayesian Estimation of Ex-Gaussian STop-Signal Reaction Time Distributions - Matzke, Dora; Love, Jonathon; Wiecki, Thomas V.; Brown, Scott D.; Logan, Gordon D.; Wagenmakers, Eric-Jan (Frontiers in Psychology, 2013)
The stop-signal paradigm is frequently used to study response inhibition. In this paradigm, participants perform a two-choice response time task where the primary task is occasionally interrupted by a stop-signal that prompts participants to withhold their response. The primary goal is to estimate the latency of the unobservable stop response (stop signal reaction time or SSRT). Recently, Matzke, Dolan, Logan, Brown, and Wagenmakers (in press) have developed a Bayesian parametric approach that allows for the estimation of the entire distribution of SSRTs. The Bayesian parametric approach assumes that SSRTs are ex-Gaussian distributed and uses Markov chain Monte Carlo sampling to estimate the parameters of the SSRT distri- bution. Here we present an efficient and user-friendly software implementa- tion of the Bayesian parametric approach —BEESTS— that can be applied to individual as well as hierarchical stop-signal data. BEESTS comes with an easy-to-use graphical user interface and provides users with summary statistics of the posterior distribution of the parameters as well various diag- nostic tools to assess the quality of the parameter estimates. The software is open source and runs on Windows and OS X operating systems. In sum, BEESTS allows experimental and clinical psychologists to estimate entire distributions of SSRTs and hence facilitates the more rigorous analysis of stop-signal data.